Diet for gout and hyperuricaemia: some important questions - O. V. Zhelyabina; M. S. Eliseev; Y. I. Kuzmina (Современная ревматология)
Diet has traditionally been viewed as playing a leading role in both the pathogenesis and treatment of gout. And although this thesis is controversial today, adherence to certain dietary rules for patients with gout and hyperuricemia (HU) is an integral part of therapy. The review examines the modern theoretical basis of dietary therapy for gout and HU, in particular the mechanisms of increasing serum uric acid levels and the risk of developing arthritis when certain foods are consumed and, conversely, reducing uric acid levels and the risk of gout when a diet containing a range of vitamins and foods in the supplements is followed.